HEALTH PROMOTION AT ORGANIZATIONAL SPACE: THE STUDY OF INTERDISCIPLINARY TEAM FOR CALL CENTER'S WORKERS. (Fiep Bulletin - online, 2013)
This research demonstrated results of two call center's groups Health Promotion Program, like former to relate interdisciplinary team's actuation, in March until September of 2008, used 1000 and 250 collaborators of metropolitan region of Campinas's(SP) and Uberlândia's(MG) units. These units was assisted for Health Promotion team (work care's professionals like: doctor, physiotherapist, hand therapist and physician's education, present only Campinas's team) and had the same initial intervention at ergonomic mapping and studies about osteomuscles disease's number. Thus, the health's interdisciplinary team take care strategic orders called Health Promotion Program. In this Program, direction for call center organization, worked for attendant work's osteomuscles disease. This systematic attendant was study and valuation workers that presented osteomuscules disease and direct away for sessions, once a week, postural orientation group and massage. In addiction, Campinas's manager demonstrated like differential news in the systematic Health Promotion Program with Physician Activity Program effect with physician's education in the special program, at three sessions a week, which work and body type. In the end six month, these results that Health Promotion Program and session with interdisciplinary team, demonstrated benefic effects in the valuation, hug and prevent practice process. In the view, the results demonstrated in the units Campinas (SP) and Uberlândia(MG), respectively, means that 80% and 40% decrease of number of osteomuscles disease and at Campinas (SP) unit had like another positive result 70% decrease of abatements and disease attested. These results sugary success of interdisciplinary work and manager in the orientation program and preventive practice for reverse disease cases, creating Life's Quality composing these call center's workers in the social and organizational context. All these orientation practice demonstrated that participative and respect action, of professional work care area in the direction for health promotion for workers and, addicting, bring complete and satisfaction results for social transformation.
Keywords: Health Promotion; Life's Quality; Interdisciplinary Team.